HUBUNGAN ADIKSI GAMES ONLINE DENGAN KETERAMPILAN SOSIAL REMAJA - Adelia Septanti; Th. Dewi Setyorini (Fakultas Psikologi Universitas Tarumanagara, 2017)
This study aims to empirically test the relationship of games online addiction with social skill in adolescents. Hypothesis proposed, there is a negative relationship games online addiction with social skill in adolescents in some games center. The total of the entire subject is 70 people. The research was used accidental sampling as a data collection technique. The data to use constructive accidental sampling. Measurement on variables social skills conducted using social skills scale of Matson namely Matson the evaluation of social skill with youngsters ( MESSY). While for games online addiction is measured using games online addiction scale. Analysis method using product moment correlation technique. Based on analysis data, have got correlation value of -0,702 ( p = 0.00 & it; 0.05 ). The result showed that there was a significant negative correlation between addiction games online with social skill. The Higher the online game addiction in adolescents, the lower social skills they have. Thus the hypothesis proposed in this study, is accepted. The test on each dimension of online game addiction shows, Conflict giving a greater effect on social skill, compared to other dimensions. The result provide additional references to similar research and confirm that dimension of conflict affecting in social skill in adolescents.Key word: social skill, online games addiction, conflict, MESSY